(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The function of the Ukrainian proverbs and sayings in the Russian press of the Ukraine is analyzed in the article. The Ukrainian proverbs and sayings are devoted as a striking example of national components in the Russian pubic texts.